Topic: assessing how the `no-jobs syndrome' affects the purchasing and consumption patterns of locally manufactured products: a case study of tertiary students from Ghana and Sierra Leone - Elijah Afeliga; Daniel E. M. Lavalie (Cogent Business & Management, 2024)
With the rising rate of youth unemployment worldwide, the situation has become unbearable, with the majority of them engaging in various social vices to sustain themselves. The governments of various nations, including Ghana and Sierra Leone, have devised a variety of policies to encourage the development of local industrial capacities, as local industrialization significantly enhances the availability of employment opportunities. These local industries are only sustained if their products are consumed, and those to lead the way should be the inhabitants through the consumption of those products. This research, therefore, sought to assess the ethnocentric tendencies of tertiary students in Ghana and Sierra Leone who are expected to be looking for jobs upon completing their programmes of study on their consumption patterns and then provided some recommendations to increase the appetite for local products. Respondents were randomly sampled and mixed-ended questionnaires were admitted. The results showed that tertiary students are aware of the unemployment situation among tertiary graduates among genders in both countries. They are also aware of the positive contribution of consumption of local products towards the creation of jobs in their localities. However, there were significant differences in gender and factors such as quality and price that could compel them to consume local products. It is therefore recommended that the government develop strategies to reduce the cost of doing business if they want to whet the appetite for the purchase and consumption of locally manufactured products without necessarily thinking that ethnocentrism will propel it. Managers of local industries should also develop and implement strategies to reduce prices and improve the quality of their operations.With the increasing rate of youth unemployment globally, life has become unbearable with most of them indulging in all manner of social vices to survive. Governments of various countries including Ghana and Sierra Leone, have developed several policies to promote local capacities in industrialization because local industrialization largely creates opportunities for job availabilities. These local industries are only sustained if indigents consume their products. This research therefore seeks to assess the consumption patterns of tertiary students who are deemed to be looking for jobs upon completing programmes of study in both countries and then propose some recommendations to increase the appetite for local products. Respondents were randomly sampled and mixed-ended questionnaires were admitted. The results showed that tertiary students are aware of the unemployment situation among tertiary graduates among genders in both countries. They are also aware of the positive contribution of consumption of local products towards the creation of jobs in their localities. However, there were significant differences in gender and factors such as quality and price that could compel them to consume local products.
Keywords: 650; consumption; ethnocentrism; purchase; employment; local products; tertiary students